Orobanche zajaciorum (Orobanchaceae): a new species from the Caucasus - Piwowarczyk, Renata (Phytotaxa, 2015)
A new, probably endemic, species, Orobanche zajaciorum (Orobanchaceae) is described from Georgia, in the Lesser Caucasus. The species grows on rocky slopes and is a parasite Scutellaria sosnowskyi. It is a small pale pink-yellowish plant, characterised by strongly curved, geniculate, white-pink flowers. A detailed description, diagnosis, and illustrations are provided.